The evolution of peripheral nerve treatment for trigeminal neuralgia - peripheral injections - Ngeow, WC; Choon, YF; Chai, WL; Tan, CC; Lim, Daniel (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Trigeminal neuralgia presents as a characteristic severe painful condition that usually afflicts the area(s) innervated by the branches of the facial sensory nerves, especially the elderly females. The diagnosis can usually be made based solely on the presenting clinical signs and symptoms. Early literatures had revealed that there have always been two major means of treatment for trigeminal neuralgia; medical and surgical. Medical treatments involved systemic intake of various drugs or the topical applications of many different materials, not forgetting that bleeding and purging has been tried in the past. The introduction of anti-convulsants during thesecond World War had changed completely the way this painful condition was treated as this therapy later become the mainstay treatment for trigeminal neuralgia. Their beneficial effects, however may not be long lasting. This review summarises the evolution of peripheral nerve injection as a treatment for trigeminal neuralgia over the last 150 years.